Building the Universal Archive of Source Code: A global collaborative project for the benefit of all. - Abramatic, Jean-François; Di Cosmo, Roberto; Zacchiroli, Stefano (Communications of the ACM, 2018)
The article discusses the collaborative source code preservation project Software Heritage, created by the French Institute for Research in Computer Science and Automation (Inria), the collection of source code using crowd-sourcing, and the preservation of the development history of the source code preserved by the project.